A aprendizagem docente e a inclusão de Cotistas B em novos contextos na universidade - Souza, Karina Silva Molon de (2016)
This study is part of the Research Line: ―Formation, Knowledge and Professional Development‖ of the Postgraduate Program in Education of Federal University of Santa Maria. The research is characterized as sociocultural narrative based on the conception of Bolzan (2001, 2006a, 2009), grounded on the studies of Vygotsky (1996, 2005, 2010), Freitas (1994, 1998, 2002), Bakthin (1992, 2010, 2011), Werstch (1993) and Connelly e Clandinin (1995). The aim of the study was to comprehend the process of learning of teaching of professors, referring to the experience of working with students with deficiency, B Quota students, at UFSM. Instruments of research were the inclusive education legislation and the narrative semistructured interview. Subjects of research were twelve professors that teach B Quota students in the context of undergraduate courses at Federal University of Santa Maria, RS. The research also proposed to recognize how the experience of pedagogical work with B Quota students influences the learning process of teaching; to know the resources used regarding personal and professional trajectories of professors that work with the inclusion of B Quota students and their implications on the process of learning of teaching; and to identify how resilience is manifested throughout the pedagogical work of university professors that work with B Quota students. Bibliographical revision of the research contemplated themes such as learning of teaching, personal and professional trajectories and resilience in teaching. The thesis produced in this study is that the learning process of university teaching, as concerns students with deficiency, happens throughout the daily work of the professors, grounded on knowledge and feelings deriving from the experience of formation. The professors who work with B Quota students, at UFSM, face a group of challenges/barriers/problems, not only regarding demands related to the deficiencies. Such challenges relate to the pedagogical work and to the constitution of the professor that learns to teach in new university contexts, in contemporaneous societies. In this scenario, professors are able to work in their specific knowledge fields, but insufficiently prepared as concerns teaching in the University context. Thus, being a professor, in emerging contexts, requires a compromise with teaching and learning processes in which B Quota students are involved, demanding willingness to live new and unpredictable experiences; striving to break the pedagogical, architectural and attitudinal barriers involving university inclusion, teaching generativity and the willingness to constantly learn; and, finally, the production of collective/shared actions that establish the protagonism of professors. Resilience in teaching is the constituting movement of being a professor that implicates in the learning of teaching as concerns professors that work with B Quota students, at University.